2003
DOI: 10.1021/nl034815s
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive Colloidal CdSe/CdS Heterostructures of Mixed Dimensionality

Abstract: We demonstrate that efficient shape control may be achieved in the shell of colloidally grown semiconductor nanocrystals (independent of the core), allowing the combination of a 0-D spherical CdSe core with a 1-D rodlike CdS shell. Besides exhibiting linearly polarized emission with a room-temperature quantum efficiency above 70%, these mixed-dimensionality colloidal heterostructures display large, length-dependent Stokes shifts as well as giant extinction coefficients approaching 10 7 cm -1 M -1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

31
660
4
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 597 publications
(702 citation statements)
references
References 26 publications
31
660
4
4
Order By: Relevance
“…The solution of CdSe seeds in TOP can be added to the reaction mixture either together with TOPS or 30-60s later, i.e., during the induction period. CdS easily nucleates at the surface of CdSe seeds [11,17]. We found that the structure of the CdSe seeds determined the morphology of CdSe/CdS nano-heterostructures.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The solution of CdSe seeds in TOP can be added to the reaction mixture either together with TOPS or 30-60s later, i.e., during the induction period. CdS easily nucleates at the surface of CdSe seeds [11,17]. We found that the structure of the CdSe seeds determined the morphology of CdSe/CdS nano-heterostructures.…”
mentioning
confidence: 84%
“…In this work we compared w-CdSe and zb-CdSe nanocrystals for seeded growth of CdSe/CdS nano-hererostructures with different morphologies. Combining CdSe and CdS in a single nanostructure creates a material with heterogeneous carrier confinement or "mixed dimentionality" where holes are confined to CdSe while electrons can move freely between CdSe and CdS phases, spreading over the entire nanostructure [11,17]. Previously we synthesized structures consisting of a spherical CdSe nanocrystal connected to a CdS nanorod [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in the colloidal synthesis of CdSe/CdS core/shell NRs, it is possible to synthesize highly efficient and crystalline CdSe/CdS core/shell NRs having a narrow size distribution by nely controlling their shape and size. 15,16 Furthermore, due to shallow band offset for electrons in the CdSe/CdS core/shell material system, a partial separation of electron and hole wavefunctions is observed which is known as the quasi type-II electronic structure that contributes to the suppression of Auger recombination, which is highly critical for achieving lasing. 11,[16][17][18] The other advantage of having a lower energy barrier for electrons in CdSe/CdS NRs is that, by simply changing their core and shell sizes, it is possible to tailor the electron and hole wavefunction overlap and tune CdSe/CdS NRs from type-I-like to quasi-type-II-like band alignment, which can be an important design consideration when engineering the gain/loss mechanisms in practical lasing systems.…”
mentioning
confidence: 99%
“…Since then, the use of fatty acid salts of zinc and elemental sulphur have been reported, but these routes require multiple injection steps. [26,27] A more attractive approach is the use of air-stable, single-source precursors, which decompose at low temperatures, yielding the desired material. Metal dithiocarbamates represent a class of compounds which decompose to yield corresponding metal sulphides.…”
mentioning
confidence: 99%